Pengembangan Sistem Informasi Kehadiran Siswa Berbasis Web (Studi Kasus: SMA Suluh Jakarta) - Ade Ayu Puspitasari; Ismiarta Aknuranda; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Suluh Jakarta High School is a private school under the auspices of the Horticulture Foundation with one of its subdivisions namely BK. BK has a role to recapitulate student attendance data, the results of recapitulation are used to monitor the percentage of student attendance. In managing the presence of students the school has not utilized technology to the fullest. Every week BK needs to recapitulate data on the attendance of students. In addition, data is not always available when needed and data is not mutually integrated. To overcome these problems, we need a technology that can help manage student attendance data, namely information systems. The information system developed can help stakeholders not need to do the recording of student attendance data because the data entered into the system will be stored and recorded automatically. The stored data will also be integrated with the data entered by the picket teacher so that data can continue to be updated. The method used to develop a Student Attendance Information System uses the waterfall model with the steps taken, namely requirements analysis, design, implementation, and testing. In order to be accessible in various places, the system developed is web-based. The results of validation testing on Student Attendance Information System obtained valid results and compatibility testing contained critical issues in the system security section in the Chrome browser and Firefox due to the use of HTTP protocol.